FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI PENYULUH AGAMA ISLAM DI KABUPATEN CILACAP - Rifa Umami; Muhtar Mochamad Solihin (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2021)
Functional Islamic Religious Extension (PAIF) and Honorary Islamic Religious Extension (PAH) are expected to have high motivation in carrying out their duties and responsibilities. This study aims to analyze the level of motivation of the PAIF and PAH, and to analyze the factors related to the motivation of the Islamic Religious Instructors. This study uses a quantitative approach with survei methods The number of samples is 65 people who are determined using the Slovin formula from a population of 184 people. Data collection uses observation, interviews, and questionnaires. Then the data is analyzed using descriptive analysis (frequency distribution and percentage) and inferential analysis. (Spearman rank correlation). The results of this study indicate that: (1) the majority of PAIF and PAH motivation levels are low. However, PAH's motivation tends to be better than PAIF's motivation in carrying out its main duties and functions; (2) the factors that are moderately related to motivation are informative support. Then the factors that are weakly related to motivation it is instrumental support and reward support. The factors that are closely related to motivation are emotional support, age, sex, education level, years of service, and the position of the assisted group.